ESG REPORTING IN THE FOCUS OF FINANCIAL MARKETS: A REVIEW OF THE SUSTAINABLE FINANCE DISCLOSURE REGULATION - Ozeran, Alla (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
This paper explores the role and impact of the Sustainable Finance Disclosure Regulation (SFDR) — Regulation (EU) 2019/2088 — within the context of ESG reporting and the broader transformation of financial market transparency. It provides an overview of the key SFDR provisions, including disclosure requirements at both the entity and product levels, and examines the classification of sustainable financial products under Articles 8 and 9. Special attention is given to the challenges associated with the initial implementation of the SFDR, such as vague terminology, the limitations of the «comply-or-explain» approach, and the absence of mandatory external audits. The adoption of the Regulatory Technical Standards (RTS) in 2022 is highlighted as a crucial development that enhanced the regulation’s clarity, comparability, and practical enforcement. The paper also discusses the SFDR’s growing indirect influence on non-EU countries, particularly Ukraine, where companies engaging with EU investors or financial institutions may increasingly be expected to align with ESG disclosure practices.